Multifunction Reflective Strap to Improve Basic Technical Skills Training for Basketball Extracurricular Participants - Laksono, Rio Puja; Pramono, Harry; Hartono, Mugiyo (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2021)
The development of basketball achievements in Indonesia begins at the school level through extracurricular activities, However, the availability of facilities and infrastructure, especially training aids, is still very lagging. Based on this, it is necessary to develop product development tools that can improve students' basketball playing skills. The purpose of this study is to produce a Multifunction Reflective Strap product that can improve basic technical skills training for basketball extracurricular participants. This research is a development research, the product development procedures consist of, conducting needs analysis to be developed, developing initial product drafts, expert validation, improvement of initial product drafts, small-scale trials, first product revisions (product revision based on the results of expert evaluation and small-scale trials), field trials (revision of the final product based on field trials), the final result in the form of Multifunction Reflective Strap media for basic technical skills training. The instruments used in this study were questionnaires, observations, interviews and documentation. The product produced in this study is named multifunction reflective strap that serves to help practice basic basketball techniques. The results of this study obtained evaluation data from basketball game experts and product assessment experts with an average percentage of 81.25% and met the